A comparison of learning preference and learning challenges between science and non-science university students / Ai-Hong Chen and Muhammad Syahiran Samsudin - Chen, Ai-Hong; Samsudin, Muhammad Syahiran (Universiti Teknologi MARA, 2022)
Due to the need for rethinking the education system designed centuries ago, it is essential to understand the current challenges of the university learning environment. We aimed to compare the learning preferences and learning challenges between science and non-science university students. 109 individuals participated in the online survey. The dependent, collaborative and independent learning preferences were inspected. The internal and external factors of learning challenges were examined jointly with social support systems, motivation, and coping styles. Both groups displayed comparable learning preferences (p>0.05) except for social media. Eight out of 17 learning challenges were significantly different between science and non-science students (p<0.05). Both groups reported analogous support systems (p>0.05) except for housemates. Similar intrinsic and extrinsic motivations were unveiled (p>0.01). Dissimilar mature and neurotic coping styles were revealed (p<0.05). In conclusion, learning preferences between science and non-science students are relatively similar, but the learning challenges vary.